Hunger Habitus: State, Society, and Starvation in Twentieth-Century Bengal - Mukherjee, Janam (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
This article offers a brief summary of the complex factors leading to the famine in Bengal in the 1940s and discusses its longer-term impacts—the afterlife, so to speak—of famine. This episode of starvation claimed as many as five million lives in Bengal, and had long lasting social, political, and economic consequences. Several different paradigms emerged that impacted the socio-political landscape of Bengal in the midst of the famine. Famine studies often focus on causality and on peaks of starvation deaths. However, periods of mass starvation such as the famine in Bengal do not simply end when mass starvation ends. Rather, famine inscribes itself into a famine society in elaborate fashion, impacting post-famine societies in abiding ways for generations to come.